Efforts to Resolve Defaults in Crossing Ticket Sale and Purchase Agreement: at Merak-Bakauheni Port - Aliyyah Fitrah Ramadan; Fadel M Diyatmo; Muhammad Zidan Diyatmo; Iis Krisnandar; Zelfi Ghaffar Aufiya (PT FORMOSA CENDEKIA GLOBAL, 2025)
Default is a form of negligence or non-conformity in carrying out obligations as required, either due to negligence or intentionality. Buying and selling is a transaction between sellers (verkoper) who intend to transfer ownership (eigendom) of an item to a buyer (koper) in exchange for a certain amount of money, as stated in Article 1457 of the Civil Code. In addition to examining the form and mechanism of dispute settlement that emerge, this study attempts to investigate the reasons that lead to defaults in the crossing ticket buy-and-sale agreement. The method used is empirical juridical with a qualitative approach, namely, examining the application of legal norms based on data and realities that occur in the field. This study also examines the role of treaty principles, including pacta sunt servanda, the principle of good faith, and the principle of legality, in determining the obligations of the parties and their legal implications. In addition, various dispute resolution mechanisms, such as negotiation, mediation, arbitration, and litigation, along with their effectiveness, were also examined. It is anticipated that the findings would further knowledge of Indonesian treaty law and dispute resolution procedures, particularly as they relate to purchasing and selling crossing tickets.